Impact of the new European respiratory (ERS)/American Thoracic Society (ATS) pulmonary function test interpretation guidelines 2021 on the interpretation of bronchodilator responsiveness in subjects with airway obstruction - Chaiwong, Warawut; Deesomchok, Athavudh; Pothirat, Chaicharn; Duangjit, Pilaiporn; Liwsrisakun, Chalerm (Respiratory medicine, 2023)
The impact of the new 2021 European Respiratory Society (ERS)/American Thoracic Society (ATS) pulmonary function test interpretation guidelines on the interpretation of bronchodilator responsiveness (BDR) in subjects with airway obstruction is still required. Therefore, the objective of this study was to explore the agreement between the 2005 and 2021 ERS/ATS criteria regarding the interpretation of the BDR. Moreover, we explore the factors that influenced the discordance of positive bronchodilator responsiveness (BDR+) between these two criteria. The agreement regarding the interpretation of BDR + between the two criteria was assessed using kappa (κ). The percentage of agreement in the interpretation of BDR + between the two criteria was calculated. The factors that influenced the discordance of BDR + between these two criteria were also analyzed. A total of 500 subjects with a mean age of 60.5 ± 15.6 years, 62.2% male were included. The study observed a good level of agreement in the interpretation of BDR + between the two criteria with kappa values = 0.782. The percentages of agreement on the interpretation of BDR + between the two criteria were high, with values = 90.6%. Male sex was the only factor that influenced the discordance of BDR + between these two criteria. A good level of agreement was observed in the interpretation of BDR + between the 2005 and 2021 criteria. Therefore, the 2005 and 2021 ERS/ATS criteria for BDR can be used interchangeably. However, the discordance of BDR + between these two criteria could be affected by sex. •The impact of the new 2021 ERS/ATS bronchodilator responsiveness (BDR) guideline is still limited.•A good level of agreement was observed in the interpretation of positive BDR + between the 2005 and 2021 criteria.•The discordance of BDR + between the 2005 and 2021 ERS/ATS could be affected by sex.